Host cell invasion by Staphylococcus aureus stimulates the shedding of microvesicles - DeWalt, Robin I. (Biochem Biophys Res Commun, 2013)
During severe sepsis, microvesicles that are positive for tissue factor (TF) are at increased levels within blood and in pulmonary lavage. These microvesicles potentially disperse TF, the major initiator of the coagulation cascade, throughout multiple organ systems, initiating fibrin deposition and resultant ischemia. The source of these microvesicles has remained incompletely defined. Although TF(+) microvesicles are shed from cells that express nascent TF transcript in response to injury, recent findings revealed that circulating, full-length TF protein is detectable prior to these nascent transcripts. This finding suggested that the protein is released from constitutive sources as an acute response. We examined whether Staphylococcus aureus, the Gram-positive bacteria that is emerging as one of the most common etiologic agents in sepsis, is capable of stimulating the release of TF(+) microvesicles from a pulmonary cell line that constitutively expresses TF protein. We found that host cell invasion stimulated an acute release of TF(+) microvesicles and that these microvesicles mediated the transfer of the protein to TF-negative endothelial cells. We also found that transfer was inhibited by cholesterol-lowering simvastatin. Taken together, our findings reveal that S. aureus pathogenesis extends to the acute release of TF(+) microvesicles and that inhibiting dispersal by this mechanism may provide a therapeutic target.